Advancing Reproductive Health through Policy-Engaged Research in Abortion Care - Munro, Sarah B.; Dunn, Sheila; Guilbert, Edith R.; Norman, Wendy V. (Seminars in Reproductive Medicine, 2022)
Mifepristone medication abortion was first approved in China and France more than 30 years ago and is now used in more than 60 countries worldwide. It is a highly safe and effective method that has the potential to increase population access to abortion in early pregnancy, closer to home. In both Canada and the United States, the initial regulations for distribution, prescribing, and dispensing of mifepristone were highly restricted. However, in Canada, where mifepristone was made available in 2017, most restrictions on the medication were removed in the first year of its availability. The Canadian regulation of mifepristone as a normal prescription makes access possible in community primary care through a physician or nurse practitioner prescription, which any pharmacist can dispense. In this approach, people decide when and where to take their medication. We explore how policy-maker-engaged research advanced reproductive health policy and facilitated this rapid change in Canada. We discuss the implications of these policy advances for self-management of abortion and demonstrate how in Canada patients “self-manage” components of the abortion process within a supportive health care system.
Keywords: abortion; Canada; health policy; implementation science; mifepristone